Electronic structure modification and negative magnetostriction in Fe-Ga alloy of D03 structure with Ga content variation - Inerbaev, Т.; Abuova, A.; Dauletbekova, А.; Abuova, F.; Zhuman, B. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
The influence of a change in the Ga content on the magnetostrictive properties of the Fe3Ga alloy with the D03 structure has been studied by density functional theory methods. The change in the stoichiometry of the alloy under study was carried out by replacing the Fe atoms with Ga. The replacement leads to a significant change in the electronic structure of the systems under study, which leads to a significant increase in the density of electronic states near the Fermi level. This effect leads to an increase in the magnetoelastic energy, which leads to an increase in the value of the magnetostrictive coefficient λ001. A further increase in λ001 occurs due to a decrease in the shear modulus, which occurs due to an increase in the number of loosening bonds in the system with an increase in the Ga content. The resulting dependence of λ001 on the Ga content, although they show an increase in the absolute value of the coefficient λ001, but give its negative values, in contrast to the positive value of magnetostriction observed in the experiment. Solving the problem of matching the sign of the theoretical and experimental values of the magnetostrictive coefficients requires further research.